2016
DOI: 10.4062/biomolther.2015.089
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coenzyme Q10Supplementation in Statin-Treated Obese Rats

Abstract: Statins, HMG-CoA reductase inhibitors, are known to cause serious muscle injuries (e.g. myopathy, myositis and rhabdomyolysis), and these adverse effects can be rescued by co-administration of coenzyme Q10 (CoQ10) with statins. The goal of the current research is to assess the efficacy of combined treatment of CoQ10 with Atorvastatin for hyperlipidemia induced by high-fat diet in SD rats. 4-week-old Sprague-Dawley male rats were fed normal diet or high-fat diet for 6 weeks. Then, rats were treated with either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Regarding CK, the present study reports that simvastatin induces CK elevation for more than 4 folds. These findings are in agreement with several other reports both in humans and animals [25][26][27][28]. Co-administration of the bee venom with simvastatin is found to partially reduce CK elevation to 2 folds only, which was still significantly high.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding CK, the present study reports that simvastatin induces CK elevation for more than 4 folds. These findings are in agreement with several other reports both in humans and animals [25][26][27][28]. Co-administration of the bee venom with simvastatin is found to partially reduce CK elevation to 2 folds only, which was still significantly high.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, myalgia is found to be the most common adverse event of statin use according to the review of MEDLINE database English articles 80 . While the mechanism by which statins produce muscle injuries is still unclear, reduction of the cholesterol content of skeletal muscle membrane is considered as a possible mechanism 81 , 82 . The other possible mechanisms include mitochondrial mechanisms 83 and inhibition of farnesyl pyrophosphate (an intermediate for the production of ubiquinone (Coenzyme Q10)) 81 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] CoQ 10 supplementation is tried in experimental studies and found to be successful in significantly reducing CK and aspartate aminotransferase levels in serum. [ 9 ] There has also been interest in the use of CoQ 10 , Chinese red rice yeast, and Vitamin D as prevention and/or management of statin-associated myopathy although there is no definite evidence.…”
Section: Discussionmentioning
confidence: 99%